SOME CONSIDERATIONS REGARDING THE EXACT SOLUTION IN THE ONE PHASE-STEFAN PROBLEM - Boucíguez, A.; Lozano, R.; Lara, M. A. (Revista de Engenharia Térmica, 2006)
The one phase Stefan problem in a semi - infinite slab with heat flux boundary condition proportional to t½ and with constant temperature boundary condition are presented here. In these two cases the exact solution exists, the relation between the two boundary conditions is presented here, and the equivalence between the two problems is demostrated.